PELAKSANAAN AUDIT OPERASIONAL ATAS PENILAIAN KINERJA FUNGSI PELAYANAN PADA PT MITRA PINASTHIKA MUSTIKA SURABAYA - Sulistyowati, Desi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purposes which is want to be achieved in this research are i.e.: (1) to comprehend the importance of the implementation of operational audit as one of performance evaluations and improvement on the service function, and to generate the improvement on the management activity or activity and the result achievement of the service function, and (2) to evaluate the function or the role of operational audit which has been carried out whether it is really effective or not for the improvement of the company in general and particularly the service function.Keywords: Operational Audit, Service Function, Effectiveness, Efficiency